Beckett's thing painting and theatre - Lloyd, David 1955- (Other Becketts, 2016)
Throughout his writing career, Beckett was deeply engaged with the visual arts and with individual painters, including Jack B. Yeats, Bram van Velde, and Avigdor Arikha. In this monograph, David Lloyd, explores what Beckett actually saw in the paintings of the painters he wrote most about and, in each case, befriended. He explains what Beckett found in the visual resources of their work rather than in the surrealism of Masson or the abstraction of Kandinsky or Mondrian, all of whose work he mentions. And he traces the common elements and developments in Beckett?s visual imagination, not only in his critical statements, but by actually looking with sustained attention at the paintings he is known to have viewed